Вryophytes of agrocoenoses of plain Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
It was found that the agrobrioflora plain in Ukraine has 45 species of bryophytes (5,4% of all species of bryophytes Ukraine). Anthocerotophyta is presented by 3 species of 2 genera family Anthocerotaceae, Marchantiophyta is represented by 5 species, 3 genera and 3 families – Ricciaceae (6,8% species composition), Cephaloziellaceae and Fossombroniaceae (2,3%), Bryophyta is presented by 37 species 21 genus 8 families. The representatives of the dominant families are the following: Pottiaceae (33,4% of species), Bryaceae (15,6%) and Funariaceae (13,3%), and Anthocerotaceae, Dicranaceae, Ditrichaceae and Ricciaceae – to 6,6% of the species composition. It is mainly heliophyte, species with life-form of loose turf, monoecious or dioecious, mesoxerophytes and mesogigrophytes, intsertophyles and calcephyles, eutrophication and mesotrophe, aridals and nemorals with holarctic or bipolar habitat.
Keywords: agrobryoflora, agrobryobiota, Ukraine, agrocoenoses.